Edible Plant Based Sensors for Real Time Health Monitoring - Drisya M K,; Fousiya K,; Akshaya Rajan P, (Asian Journal of Pharmaceutical Research and Development, 2025)
Edible plant‑based biosensors represent an emerging paradigm in non-invasive and sustainable health diagnostics. Leveraging food-grade materials such as plant-derived polymers (cellulose, pectin, starch), natural pigments (anthocyanins, chlorophyll, betalains), and edible enzymes (e.g. glucose oxidase), these ingestible systems detect physiological parameters—including gut glucose, pH, oxidative stress, and microbial activity—via colorimetric or electrochemical signals. This approach converts biomolecular interactions into quantifiable outputs through edible electrodes (e.g., activated charcoal paste), biofuel-cell energy harvesting, and RFID-like wireless telemetry. The sensors are biologically safe, biodegradable, and compatible with FDA/EFSA guidelines, providing real-time monitoring without surgical intervention. Potential applications span diabetes management, gut health diagnostics, stress and hydration monitoring, nutrient absorption profiling, foodborne pathogen detection, and precision nutrition. Key challenges include ensuring structural and functional stability in harsh gastric environments (low pH, high viscosity, peristalsis), preserving enzymatic activity during storage and digestion, scalable manufacturing of miniaturized devices, and navigating regulatory approval pathways. While many prototypes remain at proof-of-concept or preclinical stages, recent advances in eco‑friendly conductive pastes and edible microlasers signal progress toward clinical viability. Integrating these biosensors with IoT and AI platforms could enable seamless health tracking pipelines. With further research in material innovation, bioelectronic design, and clinical validation, edible plant‑based biosensors could redefine future healthcare by offering patient-friendly, eco‑conscious, and real-time internal monitoring tools.